HEMATOLOGY ANALYSIS AS A POTENTIAL TOOL TO PREDICT BONE FRACTURE IN ARABIAN RACING CAMELS (CAMELUS DROMEDARIES) - N. S. Alshamisi; T. S. Ksiksi; S. Salman Ashraf (Journal of Animal and Plant Sciences, 2013)
Racing camels (Camelus dromedaries) are historically, culturally and financially important to the United Arab Emirates (UAE). In order to develop better predictive approaches to identify at-risk animals amongst racing camels, hematological analyses of healthy (n=60), lame (n=31) and bone-fractured (n=20) camels were carried out in the present study. The hematological parameters analyzed in this study were: white blood cells (WBC, K/µL), red blood cells (RBC, M/µL), hemoglobin (HGB, g/L), mean cell volume (MCV, fL), mean cell hemoglobin (MCH, pg), mean cell hemoglobin concentration (MCHC, g/dL), platelet count (PLT, K/µL), and red blood cell distribution width (RDW, %), as well as differential leukocytic count (DLC, % neutrophil, % lymphocyte, % monocyte, % eosinophils, % basophil). Results revealed that out of the 13 parameters analyzed, 10 of the hematological parameters in females and 9 in male camels showed significant (p ≤ 0.05) differences between at least one of the groups viz. healthy vs. lame, lame vs. fractured, or healthy vs. fractured. Stepwise discriminant analysis approach was used to develop a statistical model that could distinguish healthy racing camels from lame/fractured ones. In addition to reporting baseline reference values for these hematological parameters in male and female Camelus dromedaries racing camels, our study suggests routine hematological parameters can be used to identify camels that may be at risk of developing bone fractures later in their life, thus enabling better preventive measures for these animals.
Keywords: Arabian Racing Camels; Hematology; Bone; Discriminant Analysis